Fisheries exploitation of the Halda River, Bangladesh - Arshad-Ul-Alam, Mohammad; Azadi, Mohammad Ali (Journal of Fisheries, 2016)
Fish exploitation of the Halda River was investigated for two years period from January 2007 to December 2008 to know the variation of CPUA (Catch Per Unit Area kg.ha-1year-1) among the three studied sections, months and between two years. The mean CPUA for pooled data was 295.685, 433.219, 524.449 and 411.887 kg.ha-1year-1 for the year 2007 and 415.987, 636.808, 566.515 and 527.545 kg.ha-1year-1 for the year 2008 in upstream (section 1), midstream (section 2), downstream (section 3) and over the total study area of the River Halda respectively. Analysis of variance showed highly significant difference of CPUA among gears and months. No significant difference of CPUA was observed among sections. Combined CPUA during 2008 observed higher and statistically significant than previous year.